Design, synthesis and evaluation of inhibitors of POT1-DNA interactions - Malik, Adnan Mahmood (2013)
The unlimited replicative potential of cells is one of the hallmarks of cancer. Telomeres, DNA structures found at the ends of chromosomes have attracted a great deal of interest in recent years as potential anti-cancer drug targets since they play an important role in cancer cell immortality.